Evolution of 3-D Transport Pathways and Triple-Phase Boundaries in the Ni-YSZ Hydrogen Electrode upon Fuel Cell or Electrolysis Cell Operation. (30th May 2017) - Nakajo, Arata; Cocco, Alex P.; DeGostin, M. B.; Burdet, Pierre; Peracchio, Aldo A.; Cassenti, Brice N.; Cantoni, Marco; Van herle, Jan; Chiu, Wilson K. S.
Abstract : The degradation of the Ni-YSZ electrode was investigated after SOFC or SOEC operation for up to 4, 700 h and 10, 700 h, respectively. 3-D FIB-SEM serial sectioning, combined with 3-D EDS elemental mapping allowed the measurement of structural, material and electrochemical properties. Ni coarsening was observed during SOFC and SOEC operation. In SOFC, the comparison of EIS measurements and Electrochemical Fin theory simulations suggested that degradation was mainly due to a decrease in the connected TPB length. However, longer aging time should be investigated. In SOEC, large microstructural alterations were observed with the depletion of Ni close to the YSZ electrolyte. The average connected TPB length was not significantly affected possibly because of finer Ni, but local variations were observed. Accessible TPB length calculations indicate that the access of TPBs by electrons and ions is less efficient, which is likely due to the modified spatial distribution of the TPBs.